Detection of Dengue Virus in Female Aedes aegypti Mosquito using Reverse Transcription-polymerase Chain Reaction (RT-PCR) in West Jakarta - Paiman, Dessy; Setiani, Ony; Budiyono, Budiyono (Poltekkes Kemenkes Palu, 2024)
Dengue hemorrhagic fever (DHF) is an acute disease caused by dengue virus infection which is a clinical manifestation of bleeding, transmitted through the bite of a female mosquito Aedes aegypti. The incidence of dengue fever is still a health problem in developing countries, including Indonesia. There are several ways to detect the presence of dengue virus, namely by Reverse Transcription-Polymerase Chain Reaction (RT-PCR). The purpose of this study was to detect Dengue virus in adult female Aedes aegypti mosquitoes using RT-PCR. The type of research is a descriptive survey to determine the number of dengue virus transmission in Aedes aegypti mosquitoes in Kembangan Village, West Jakarta, especially in RW02 RT 1-10. There are 62 Aedes aegypties found in 100 houses that were selected by simple random sampling. Totally 23 female Aedes aegypties were identified from a total of 62. Moreover, the result showed that all Aedes aegypti mosquitoes caught in were negative for dengue virus. There are several reasons for the limitation of RT-PCR that caused zero findings, including potential false negatives, sensitivity, low quality control measures. Moreover, the small sample size and seasonal reason also played a role in impacting the zero result.